The landscape of bacterial contractile injection systems across large-scale metagenomes - Shang Li; Jiacheng Wu; Qinghua Wang; Hongqian Cao; Lei Zhang (Microbiology Spectrum, 2025)
ABSTRACT Bacterial contractile injection systems (CISs) have evolved as sophisticated mechanisms that enable bacteria to interact with and manipulate their hosts. Resembling bacteriophage tails, these systems inject effector proteins directly into target cells, facilitating complex bacterial-host interactions. Despite significant advances in understanding CISs, exploration has largely been constrained by the availability of completely sequenced microbial genomes, potentially underrepresenting their diversity in natural environments. In this study, we identified 1,129 CISs from metagenome-assembled genomes spanning 14 bacterial phyla and 1 archaeal phylum. Notably, CISs were identified in many uncultured microorganisms and were highly enriched in the phylum Bacteroidota. Structural gene composition varied across ecosystems, with Bacteroidetes injection systems (BISs) from the human digestive system lacking typical tail fiber proteins and Cis6. However, all BISs encoded homologs of Aasi_0556, suggesting functional similarities with T6SSiv. Furthermore, we identified a candidate CIS cargo protein, BDI_2459, containing the toxin-associated DUF4157 domain, which exhibited moderate toxin potential. We cloned and heterologously expressed BDI_2459 in Escherichia coli. The standalone BDI_2459 did not exhibit its activity. However, there was activity when fused with a periplasmic translocation tag.IMPORTANCEOverall, this study expands our understanding of the ecological diversity, evolutionary adaptations, and functional roles of contractile injection systems (CISs) in microbial communities. The findings particularly highlight their adaptations to human-associated microbiomes. In addition, we conducted preliminary functional studies targeting the cargo protein BDI_2459 in CIS from Parabacteroides distasonis (CISPd). These results provide new insights into CIS-mediated bacterial interactions and pave the way for future microbiome engineering and antibacterial strategies.